Effect of microbial biopolymers on the sedimentation behavior of kaolinite - Kwon, Yeong Man; Kang, Seok Jun; Cho, Gye Chun; Chang, Ilhan (Geomechanics and Engineering, 2023)
Clay sedimentation has been widely analyzed for its application in a variety of geotechnical constructions such as mine tailing, artificial islands, dredging, and reclamation. Chemical flocculants such as aluminum sulfate (Al2(SO4)3), ferric chloride (FeCl3), and ferric sulfate (Fe(SO4)3), have been adopted to accelerate the settling behaviors of clays. As an alternative clay flocculant with natural origin, this study investigated the settling of xanthan gum-treated kaolinite suspension in deionized water. The sedimentation of kaolinite in solutions of xanthan gum biopolymer (0%, 0.1%, 0.5%, 1.0%, and 2.0% in a clay mass) was measured until the sediment height was stabilized. Kaolinite was aggregated by xanthan gum via a direct electrical interaction between the negatively charged xanthan gum molecules and positively charged edge surface and via hydrogen bonding with kaolinite particles. The results revealed that the xanthan gum initially bound kaolinite aggregates, thereby forming larger floc sizes. Owing to their greater floc size, the aggregated kaolinite flocs induced by xanthan gum settled faster than the untreated kaolinite. Additionally, X-ray computed tomography images collected at various depths from the bottom demonstrated that the xanthan gum-induced aggregation resulted in denser sediment deposition. The findings of this study could inspire further efforts to accelerate the settling of kaolinite clays by adding xanthan gum.
Keywords: Artificial islands; Deionised waters; Electrical interaction; Floc size; Geotechnical; ITS applications; Mine tailings; Negatively charged; Positively charged; Settling behavior; coagulation; flocculation; kaolinite; sedimentation; xanthan gum